An international perspective of the academic-practitioner divide in advertising: an exploratory study into its causes and solutions. Issue 1 (2nd January 2023) - Ang, L.; Buzeta, C.; Hirose, M.; van Loggerenberg, M. J. C.; van Noort, G.; Uribe, R.; Voorveld, H. A. M.
Abstract: In our international study of seven countries, we found that the academic-practitioner divide is as real today as it was three decades ago. The divide, which is more pronounced in some regions, is likely to worsen as society becomes more digitally complex, exacerbated by the lack of industry experience among young scholars entering academia in some quarters. Many bridging solutions were explored in this study, but the most important solution is for academia to produce relevant research, one that is useful for the industry. This should be widely and innovatively disseminated in a way that is easy to understand without dumbing it down. Practitioners generally do not like or know how to collaborate with academics, suggesting a need to develop a culture or mechanism that can raise awareness and foster mutual respect and trust between academia and industry. Bridging the divide will be challenging because of the existing academic reward structures. This situation needs to change. The discovery of two successful research institutes in the Netherlands and Australia shows how this divide can be bridged.